Population Analysis of the Settlement Movement in Western Canada - Antonie, Luiza; Baskerville, Peter; Grewal, Gary; Turcotte, Benjamin (International Journal of Population Data Science, 2018)
Introduction The Canadian settlement of the west, via granting free homesteads, is perhaps one of the largest public policy undertakings in the nation's history. However, little is known about the homesteaders themselves, where they came from, how long they stayed and the settlement environment that was created at the time. Objectives and Approach This research adopts a detailed population analysis of the settlement movement in Western Canada. In addition to outlining the social and economic characteristics of the homesteaders, the project answers the following central question: Did it create a stable society of settlers or did it create a field for speculative investment? The data consist of machine readable individual level databases containing detailed information on and stories from circa 170,000 Alberta homesteaders. These homesteaders will be individually linked to three twentieth century Canadian censuses and the Canadian Pacific Railway's land records to provide an unprecedented holistic analysis of Alberta's early European population. Results We report on the linkage methodology used to integrate all these data sources. In addition, we discuss any particular issues we encountered given the nature of the historical data. We describe the data cleaning and standardization that was undertaken to facilitate the linkage process. We present and discuss the linkage results obtained, how much of the population was linked and what are the characteristics of those we couldn’t link. We expect that this research will shed new light on persistence rates, trajectories of family composition, nature of labour market adjustment, degrees of social/gender inequality and impacts on regional development. The results will challenge many myths concerning homesteaders and their impact on western Canada and in the process provoke renewed discussion of western Canadian history. Conclusion/Implications The research will inform and be informed by work currently being undertaken on migration patterns at the international level. Finally the research has implications for understanding the legacies of rapid population movements, state formation, public policy and national identities in the present.